The Effectiveness Of Video Media In Increasing Knowledge About Caries In Children With Light Impossible At Slb Putra Mandiri - Prasetyowati, Silvia; Berliana Effrianti; Siti Fitria Ulfah; Endang Purwaningsih (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Background: Mentally retarded children are identified as having a low level of intelligence. Mentally retarded children are one of the criteria with the most people who are vulnerable to exposure to disease. Mental retardation usually has a higher prevalence of caries, gingivitis and periodontal disease compared to children of the same age. The 2018 Riskesdas results explain that the proportion of dental and oral problems in Indonesia has increased from 23.2% in 2007 to 57.6%, so counselling is needed for dental and oral health with aids or media that can attract children's interest. Research Objectives: To know the effectiveness of video media in increasing knowledge about caries in children with mild mental retardation at Putra Mandiri SLB. Research Methods: Using a Quasi-Experimental design with a Control Group Pre-Test – Post-Test design. Data analysis: Using a simple random sampling technique or taking samples from the population taken randomly with a population of 25 students and a sample of 24 students. Data Collection Method: Observing the results of counselling with video media in increasing caries knowledge in children with mild mental retardation using a questionnaire. Research Results: There is a significant effect of providing video media interventions on increasing the knowledge of mentally retarded children. Conclusion: Health education with video media about dental caries is effective in increasing the knowledge of children with mild mental retardation.